Krisis Hiperglikemik: Diabetic Ketoacidosis (DKA) dan Hyperglycemic Hyperosmolar State (HHS) - Wibowo, Muhammad Rafi; Rudiyanto, Waluyo; Yunianto, Andi Eka; Soleha, Tri Umiana (CV. Jasa Sukses Abadi, 2024)
Hyperglycemic crisis is an acute metabolic complication of diabetes mellitus that can be life threatening if not treated appropriately. This research aims to examine in more depth the hyperglycemia crisis. This research is a literature study using relevant literature such as articles and journals from various national and international databases such as Google Scholar, NCBI, and PubMed. Diabetic Ketoacidosis (DKA) and Hyperglycemic Hyperosmolar State (HHS) are serious and emergency forms of hyperglycemic crisis. DKA is often found in people with type 1 diabetes due to severe insulin deficiency, which is characterized by the triad of hyperglycemia, acidosis, and ketosis. In contrast, HHS occurs more frequently in type 2 diabetes, with features of hyperglycemia, hyperosmolarity, and dehydration, but without significant ketosis and acidosis. Both of these conditions have a high risk of death if left untreated, with the death rate for DKA around <1% and HHS around 15%. The goal of treatment for both is to improve circulation and tissue perfusion, correct hyperglycemia, ketogenesis, and electrolyte imbalances, and identify precipitating factors. Treatment begins with correcting dehydration and electrolyte imbalances through rehydration with crystalloid fluids, as well as treating hyperglycemia by administering insulin boluses or infusions. Prevention of DKA and HHS is to ensure that patients do not stop insulin or oral hyperglycemic drugs, monitor blood sugar levels regularly and immediately seek professional medical help if something undesirable happens.